A route for the top-down fabrication of ordered ultrathin GaN nanowires. (1st March 2023) - Oliva, M; Kaganer, V; Pudelski, M; Meister, S; Tahraoui, A; Geelhaar, L; Brandt, O; Auzelle, T
Abstract: We introduce a facile route for the top-down fabrication of ordered arrays of GaN nanowires with aspect ratios exceeding 10 and diameters below 20 nm. Highly uniform thin GaN nanowires are first obtained by lithographic patterning a bilayer Ni/SiN x hard mask, followed by a combination of dry and wet etching in KOH. The SiN x is found to work as an etch stop during wet etching, which eases reproducibility. Arrays with nanowire diameters down to (33 ± 5) nm can be achieved with a uniformity suitable for photonic applications. Next, a scheme for digital etching is demonstrated to further reduce the nanowire diameter down to 5 nm. However, nanowire breaking or bundling is observed for diameters below ≈20 nm, an effect that is associated to capillary forces acting on the nanowires during sample drying in air. Explicit calculations of the nanowire buckling states under capillary forces indicate that nanowire breaking is favored by the incomplete wetting of water on the substrate surface during drying. The observation of intense nanowire photoluminescence at room-temperature indicates good compatibility of the fabrication route with optoelectronic applications. The process can be principally applied to any GaN/SiN x nanostructures and allows regrowth after removal of the SiN x mask.